DISCUSSIONS ON THE JUST WORLD ORDER IN TURKEY: COMPARATIVE ANALYSIS OF CONCEPTS AND FOREIGN POLICY PRACTICES OF THEIR IMPLEMENTATION IN THE 2000’s - P. V. Shlykov (Сравнительная политика)
The international transformations, which the Middle East faced in the 20th and early 21st centuries, virtually made it a region without any regional order. Polycentric structural organization, an intrinsic feature of the Middle East, has resulted in multiple visions of regional order generated by regional powers and global actors actively involved in the regional affairs. Paradoxically, however, none of these powers had enough military, political, cultural or ideological potential to implement its vision and impose it on others. Against this background Turkey’s foreign policy strategy had signifi cantly changed at the turn of the centuries. In the later 1990s Turkey was still a status quo power, dependent on its relations with the West and adherent to the principles of non-interference in the regional affairs. However, its rising involvement in global and regional affairs in the fi rst decade of this century made Ankara’s foreign policy much more liable to international and regional developments. In addition, the advent to power of the Justice and Development Party added a strong Islamic element to its domestic and foreign policy discourse. As a result during the fi rst decade of this century Turkey undertook an effort to propose its own version of regional order based on the convergence of liberal and Islamic values. The Arab Spring and a new wave of regional destabilization however seriously limited Turkey’s ability to do it. Reacting to the regional turbulence Turkey has reset its foreign policy appealing to the concept of “moral realism”, an intricate combination of humanitarianism and militarism being its core part.